STUDI KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DALAM PELAKSANAAN EVALUASI PEMBELAJARAN - Hasibuan, Hamdan (AIN Padangsidimpuan, 2016)
Teacher competency is the ability, expertise and skills that should be possessed by teachers in carrying out the learning process that includes lesson plans. Implementation of learning is until the evaluation. In terms of evaluation, a teacher is said to be competent to understand the technique and evaluation procedures, and able to carry out the evaluation in order to get the results. The evaluation is used to improve the teaching and learning process. The evaluation starts from planning evaluation, test item construction, process and analysing the test results to interpret and follow up on the results of the evaluation.